Challenges faced by women employees of Working from Home (WFH) during COVID-19: a case study in Honda Malaysia Sdn Bhd Alor Gajah Melaka / Anis Atihrah Karim Johari and Nur Aryannie Ahmad - Karim Johari, Anis Atihrah; Ahmad, Nur Aryannie (2022)
Working from home has posed various challenges to those who experienced, especially women employees. This is due to burden of many responsibilities as a wife, mother, daughter and employees, inadequate working equipment or even no proper work-space at home. Because of that, this study aimed to discuss the challenges faced (psychological, physical, technological) by women employees of working from home and the impact on their wellbeing. Cross sectional design was employed to conduct the findings and simple random sampling has been used in collecting the data. The population involved in this study was women employees from Honda Malaysia Sdn Bhd, Alor Gajah Melaka. Around 148 valid responses were received from the survey and the results were analyzed by using descriptive statistic (mean, frequency, percentage) and simple linear regression. The outcome of the findings revealed, most women employees aware that they faced more challenges while working from home and they agreed on planning a proper working space to work comfortably at home as their coping strategies. However, this study shows that challenges of working from home (psychological, physical, technological) has no significant relationship towards the impact on employee wellbeing.